Haematological and Serum Biochemical Indices of Naked Neck and Normally Feathered Nigerian Indigenous Chickens in a Sub Humid Tropical Environment - Ladokun, A.O.; Yakubu, A.; Otite, J.R.; Omeje, J.N.; Sokunbi, O.A.; Onyeji, E. (International Journal of Poultry Science, 2007)
Haematological and serum biochemical indices of Nigerian indigenous chickens of two genetic groups were evaluated. One hundred and twenty (120) cocks with average weight of 1.10kg, corresponding to sixty (60) naked neck (NaNa) and sixty (60) normally feathered (nana) were utilized in the study. On the basis of feather colour, the normal plumage cocks were subdivided into two equal phenotypic groups. Each genetic group was divided into four replicates of fifteen birds each in a completely randomized design. There were no significant (P>0.05) differences between the genotypes in the mean values of white blood cells(WBC), mean corpuscular volume(MCV), mean corpuscular haemoglobin concentration(MCHC). However, naked neck cocks were significantly superior in packed cell volume (PCV) haemoglobin (Hb) and red blood cells(RBC) compared with their normally feathered counterparts(41.00 vs 35.90%; 13.68 vs 11.60 g/dl; 4.84 vs 4.21x106/ml; p>0.05). With the exception of PCV which was significantly (p>0.05) higher in brown cocks than white coloured cocks (38.30 vs 33.50%), plumage colour had no significant effect on the variables estimated. No significant differences were observed in total protein, albumin, urea, glucose, cholesterol, serum alanine amino transaminase (SALT) and serum aspartate amino transferase (SAST) of the genetic groups. The normally feathered cocks, however had significantly (P0.05) affect serum biochemical parameters suggesting that the two colour variants might not be true representation of genetically distinct subpopulations. The present result on blood parameters of both naked neck and normally feathered cocks could serve as a baseline data, which could be exploited in the improvement of local stock.